Anelja Katkovič, Veranika Katkovič-Klentak "Uspamìny" - Charytoniuk-Michiej, Grażyna; Katkovìč, Anelâ (1914-1982).; Katkovìč-Klentak, Veranika (1918- ). (2000)
Recenzja książki.
Nazwa aut. recenzji pod tekstem.
Keywords: Katkovìč, Anelâ -- (1914-1982) -- biografie; Książki -- recenzje -- 1990-.